Cognitively inspired audiovisual speech filtering : towards an intelligent, fuzzy based, multimodal, two-stage speech enhancement system /: towards an intelligent, fuzzy based, multimodal, two-stage speech enhancement system. (2015) - Abel, Andrew; Hussain, A (Amir)
No abstract available